Mixed Integration of CDIO skills into Telecommunication Engineering Curricula - Sayrol, E.; Bragós, R.; Alarcón, E.; Cabrera, M.; Calveras, A.; Comellas, J.; O’Callaghan, J.; Pegueroles, J.; Pla, E.; Prat, L.; Sáez, G.; Sardà, J.; et al. (Elektronika ir Elektrotechnika, 2010)
Spain has been intensively involved in designing engineering curricula for the last two years and next academic year all engineering schools will be deploying all bachelor programs adapted to the EHEA and to the Spanish laws. The different frameworks that set the conditions of the process of drawing up new curricula emphasize the use of competency-based learning and the insertion of certain generic skills within the structure of the new plans. In the school of Telecommunication Engineering of Barcelona, the CDIO initiative (Conceive-Design-Implement-Operate) first developed jointly by MIT and some Swedish Universities, has been chosen as paradigm for new engineering curricula design. We used a mixed approximation to integrate CDIO skills into the study plans. In this paper we will explain the approach to include generic skills when designing new curricula.